The Dialectics of Melancholy and Nostalgia in Apophatic Marxism - Genovese, Taylor R. (Political theology, 2025)
Following the provocation put forth by China Miéville in which he proposed the development of an "apophatic Marxism," this article seeks to advance his suggestion of transmuting Marxism beyond the baggage of its historical experimentation and substantively putting it to work within our present material conditions. In this article, I argue that unlike cataphatic Marxist analyses of the past, the apophatic way is one that is better primed to take seriously the unique plethora of aporias and uncertainties that seem to define the twenty-first century. In particular, I propose that a critical engagement with affects such as melancholy and nostalgia allow us to learn from past political motivations as well as discover and develop liberatory tactics better attuned to the advantages of an intersectional praxis.